Insights Into IoT: A Bibliometric Study Revealing The Development of Smart Home Technologies in Scholarly Conversation - Fitri, Fitri Syifa Ummi; Sumantri, Lugi (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis explores the ever-changing field of Internet of Things (IoT) research, with a particular emphasis on how smart home technologies have developed in academic discourse. We uncover important trends, significant figures, and developing topics influencing the story of IoT in smart homes by thoroughly examining scholarly papers. Our study covers a certain time period and provides insights on the direction of research, technical developments, and the relationship between security and innovation. We map the intellectual environment using bibliometric approaches, which helps researchers, practitioners, and policymakers navigate the complex world of IoT-enabled smart homes.